Investigating and implementing a student vocational education model for educational innovation - Ho, Van-Thong; Tran, Huy-Hoang; Nguyen, Van-De; Nguyen, Van-Trang (Journal of Education and e-Learning Research, 2023)
The development of each student's awareness serves as the governing principle for high school vocational education programs. This awareness then becomes the driving force behind the progression of the educational process. Career education activities for students are the relationships between the objectives, contents, methods and forms of organization of educational activities that are directly and constantly influenced by the educational environment. Student career education activities are the relationships between these aspects of educational activities as determined by research into the programs, textbooks, systematization and theoretical analysis of these activities. This investigation focuses on the following areas: (1) Developing preschool and high school teachers in the province of Dong Thap to meet the criteria of the new educational program (2) Developing models of applying local educational material for students in the province of Dong Thap. Both of these initiatives are part of the Dong Thap Educational Development Project. Findings: Assess the current state of activities for students in the province of Dong Thap that are related to vocational education between 2018- 2021. Develop a model for carrying out activities for students participating in vocational education in the province of Dong Thap to fulfill educational innovation requirements.